Dielectric material, multilayer ceramic capacitor and preparation method thereof

By controlling the particle size distribution of dielectric powders of three different particle sizes, the tight accumulation of dielectric powder is achieved, which solves the problems caused by the traditional dielectric layer thickness limitation and the reduction of dielectric powder size, and improves the density and reliability of multi-layer ceramic capacitors sex.

CN119517619APending Publication Date: 2025-02-25德阳三环科技有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560803.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The thickness of the traditional dielectric layer limits the maximum capacity of the capacitor, and the reduction in the dielectric powder size leads to lower dielectric constant, increased cost, and poor film tape density and reliability.

Method used

By controlling the particle size distribution of three different particle sizes of medium powder A, medium powder B and medium powder C, the close packing between powder particles is achieved and the filling density of the medium material is improved.

Benefits of technology

The density of the dielectric film tape and the reliability of the multi-layer ceramic capacitor are improved, the compressed deformation amount and production cost are reduced, and the problems of serious deformation of the film tape and product short-circuit rate are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517619A_ABST
    Figure CN119517619A_ABST
Patent Text Reader

Abstract

The invention discloses a dielectric material, a multilayer ceramic capacitor and a preparation method thereof, and relates to the technical field of dielectric materials. The dielectric material comprises dielectric powder A, dielectric powder B and dielectric powder C, the average particle sizes of the medium powder A, the medium powder B and the medium powder C are RA, RB and RC respectively; wherein RA > RB > RC; the particle size distribution of the medium powder A, the medium powder B and the medium powder C meets the following relation: the maximum particle size is 2-2.5 times of the average particle size; the minimum particle size is 1 / 4-1 / 3 of the average particle size. According to the dielectric material, close packing is formed through grading, the problem that dielectric powder is not tightly packed is solved, and the compactness and reliability of a film belt can be improved when the dielectric material is used for a multilayer ceramic capacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dielectric materials, and in particular to a dielectric material, a multilayer ceramic capacitor and a preparation method thereof. Background Art

[0002] With the rapid development of modern electronic technology and the continuous growth of demand, multilayer ceramic capacitors have become an important innovation due to their large capacity and small size. They are widely used in key areas such as energy storage, filtering, and signal coupling in electronic circuits. With the continuous development and enhancement of electronic equipment, as well as their miniaturization, the demand for capacitor capacity is also increasing, but the thickness of the traditional dielectric layer limits the maximum capacity of the capacitor. In order to reduce the thickness of the dielectric layer, a common method is to reduce the size of the dielectric powder. However, as the thickness of the dielectric layer decreases, the preparation of a thinned dielectric layer by simply reducing the size of the dielectric powder usually leads to problems such as a decrease in dielectric constant and increased cost. At the same time, due to the loose stacking of the dielectric powder, it is inevitable that problems such as severe deformation of the film strip, high product short circuit rate, poor stability and reliability will occur. Summary of the invention

[0003] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention aims to provide a dielectric material, which controls the particle size distribution of the powder so that powder particles of different particle sizes can be matched to form a dense stack.

[0004] A second aspect of the present invention is to provide a dielectric slurry.

[0005] A third aspect of the present invention is to provide a multilayer ceramic capacitor.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: The first aspect of the present invention provides a dielectric material, including dielectric powder A, dielectric powder B and dielectric powder C; the average particle sizes of the dielectric powder A, dielectric powder B and dielectric powder C are R A , R B , R C ; Among them, R A >R B >R C ; The particle size distributions of the medium powder A, medium powder B, and medium powder C all satisfy the following relationship: The maximum particle size is 2 to 2.5 times the average particle size; The minimum particle size is 1 / 4~1 / 3 of the average particle size. According to the gradation theory, when particles of various discrete particle sizes are piled up, when the particle size distribution meets certain conditions, small particles can fill the gaps of large particles, thereby increasing the packing density of the powder particle size. When dielectric materials are applied to multilayer ceramic capacitors, if the packing density of dielectric powder can be increased, on the one hand, the fluidity of the slurry can be improved under the effect of "small balls boosting and large balls assisting flow", and on the other hand, the increased density can reduce the linear expansion coefficient of the material and improve the sintering shrinkage and thermomechanical properties of the capacitor.

[0007] When a powder with a particle size distribution is used to prepare a dielectric slurry for production, there will be large gaps between the powder particles, and the filling between each other is not tight enough, so the density of the prepared dielectric film is poor. However, the particle size of most dielectric materials currently used for high-capacity multilayer ceramic capacitors is less than 250nm. At this time, if a two-graded dielectric material is used, that is, two dielectric powders with different particle sizes are mixed, the degree of densification is still low, and the use of a four-graded dielectric material will cause the finest powder particle size to reach 10nm level, greatly increasing the production cost. The present invention models the dielectric material and simplifies it into a sphere. The particle size distribution of the dielectric material is finally determined based on the geometric relationship of the gradation theory. By mixing three powders of different particle sizes and controlling the particle size distribution of the powder, tight stacking can be achieved. When applied to multilayer ceramic capacitors, the density of the dielectric film can be improved, thereby improving the performance of the product.

[0008] The dielectric material used in the present invention includes three different particle sizes of dielectric powder A, dielectric powder B and dielectric powder C, and the particle size distribution requirements are as follows: the maximum particle size is 2 to 2.5 times the average particle size, and the minimum particle size is 1 / 4 to 1 / 3 of the average particle size. If the relationship between the maximum particle size and the minimum particle size of a dielectric material and the average particle size does not satisfy the above relationship, it will cause the normal distribution of the three powder particle sizes to overlap too much, ultimately resulting in low film density and large compression deformation, which will ultimately affect the performance of multilayer ceramic capacitor (MLCC) products.

[0009] Preferably, the R A , R B , R C Satisfy at least one of the following a)~b): a) R A / R B =2~2.8; b) R A / R C =9~9.6.

[0010] More preferably, the R A / R B =2.2~2.6, and more preferably 2.2~2.5.

[0011] More preferably, the R A / R C =9.2~9.4.

[0012] Preferably, the average particle size R of the medium powder A is A It is 80~300nm.

[0013] More preferably, the average particle size R of the medium powder A is A It is 120~220nm.

[0014] Preferably, the average particle size R of the medium powder A is A It is 190~210nm.

[0015] Preferably, in the dielectric material, the mass content of dielectric powder A is 91-96%.

[0016] More preferably, in the dielectric material, the mass content of dielectric powder A is 91.9-95.9%.

[0017] More preferably, in the dielectric material, the mass content of dielectric powder A is 93-95%.

[0018] Preferably, in the dielectric material, the mass content of dielectric powder B is 4-9%.

[0019] More preferably, in the dielectric material, the mass content of the dielectric powder B is 5-7%.

[0020] Preferably, in the dielectric material, the mass content of dielectric powder C is 0.08-0.2%.

[0021] More preferably, in the dielectric material, the mass content of the dielectric powder C is 0.1-0.15%.

[0022] More preferably, in the dielectric material, the mass content of dielectric powder C is 0.1-0.12%.

[0023] In the process of mixing medium materials, if the powder is added without following the above mass ratio, it will lead to deviation from the preset powder stacking state, which is not conducive to achieving the most dense stacking state.

[0024] In the present invention, when the average particle size and mass ratio of the three dielectric powders are lower than the lower limit of the range, the gaps of the dielectric powders will not be fully filled, resulting in insufficient density of the ceramic green sheet; when the average particle size and mass of the three dielectric powders are greater than the upper limit of the range, that is, the average particle size of dielectric powders B and C is larger than the requirement or the amount added is too much, when they are filled in the pores of dielectric powder A, it will affect the stacking of dielectric powder A, and also cause the density of the membrane tape to decrease, and even be lower than the stacking density of powders with a single particle size. At the same time, since the average particle size of dielectric powders B and C is relatively small, small-particle powders are more difficult to disperse, and after a large amount is added, they are prone to agglomeration and sedimentation, resulting in uneven casting surface density, and also poor slurry fluidity, ultimately deteriorating product reliability.

[0025] Preferably, when the dielectric material is applied to a ceramic capacitor, the thickness of the formed ceramic green sheet satisfies the following relationship: 0.1T≤R A ≤0.2T; more preferably 0.14T≤R A ≤0.16T.

[0026] Preferably, the dielectric powder A, dielectric powder B and dielectric powder C are independently selected from at least one of barium titanate, strontium titanate, barium zirconate, strontium zirconate and barium strontium zirconate titanate.

[0027] The second aspect of the present invention provides a dielectric slurry, comprising the dielectric material described in the first aspect of the present invention.

[0028] Preferably, the medium slurry further comprises a dispersant, a binder, an organic solvent, a plasticizer, a defoamer and a grinding medium.

[0029] More preferably, the dispersant includes at least one of sodium methylene naphthalene sulfonate, polyacrylic acid, and polyacrylamide; the binder includes at least one of polyvinyl butyral resin, polymethyl methacrylate, and polypropylene resin; the organic solvent includes toluene and / or ethanol, and the volume ratio of toluene to ethanol is (4~6):(6~4); the plasticizer includes at least one of dioctyl phthalate and dibutyl phthalate; the defoamer includes at least one of polydimethylsiloxane, ethylene oxide, and trialkyl melamine; and the grinding medium includes at least one of zirconium dioxide grinding balls and aluminum oxide grinding balls.

[0030] Preferably, the medium slurry comprises the following components by mass: 100 parts of medium material, 0.05-0.1 parts of dispersant, 20-30 parts of adhesive, 20-35 parts of organic solvent, 0.05-0.1 parts of plasticizer, 0.05-0.2 parts of defoamer, and 5-20 parts of grinding media.

[0031] More preferably, the medium slurry comprises the following components by mass: 100 parts of medium material, 0.06-0.1 parts of dispersant, 20-30 parts of binder, 20-35 parts of organic solvent, 0.05-0.1 parts of plasticizer, 0.08-0.15 parts of defoamer, and 5-18 parts of grinding media.

[0032] More preferably, the medium slurry comprises the following components by mass: 100 parts of medium material, 0.07-0.09 parts of dispersant, 23-28 parts of binder, 20-30 parts of organic solvent, 0.07-0.09 parts of plasticizer, 0.08-0.12 parts of defoamer, and 10-20 parts of grinding medium.

[0033] Preferably, the method for preparing the medium slurry comprises the following steps: The medium materials are mixed, and a dispersant, a binder, an organic solvent, a plasticizer, a defoamer and a grinding medium are added and mixed to obtain the medium slurry.

[0034] More preferably, the medium powder A, medium powder B and medium powder C in the medium material are mixed for 4 to 8 hours.

[0035] More preferably, the method of adding the dispersant, adhesive, organic solvent, plasticizer, defoamer and grinding medium for mixing comprises sand milling; the sand milling time is 8 to 16 hours, more preferably 8 to 12 hours.

[0036] The third aspect of the present invention provides a multilayer ceramic capacitor, comprising the dielectric material described in the first aspect of the present invention, or the dielectric slurry described in the second aspect of the present invention.

[0037] Preferably, the multilayer ceramic capacitor further comprises a ceramic green sheet formed by a dielectric slurry; the average particle size R of the dielectric powder A is A The thickness of the ceramic green sheet T satisfies the following relationship: 0.1T≤R A ≤0.2T.

[0038] When a ceramic green sheet is formed by a tape casting process, the ceramic green sheet is also called a film tape, which is a strip-shaped object formed by slurry tape casting.

[0039] More preferably, the average particle size R of the medium powder A is A The thickness of the ceramic green sheet T satisfies the following relationship: 0.14T≤R A ≤0.16T, i.e. 0.14≤R A / T≤0.16.

[0040] In the multilayer ceramic capacitor of the present invention, the average particle size R of the dielectric powder A is A Satisfy 0.1T≤R A ≤0.2T, R AToo small relative to the green sheet thickness, that is, R A When / T<0.1, it is equivalent to that there are more fine powder particles in a film strip, which will lead to high sintering activity during the preparation process, making the sintering temperature and atmosphere range smaller, thereby reducing the product qualification rate and increasing the cost; R A Too large relative to the green sheet thickness, that is, R A When / T>0.2, it is equivalent to that the powder particles in the film tape are larger, which will cause the surface roughness of the cast film tape to be large, the density of the film tape to decrease, and the interlayer bonding strength, consistency of electrical properties and reliability of the product to be reduced.

[0041] Preferably, the thickness T of the ceramic green sheet is 0.5 μm≤T≤50 μm.

[0042] More preferably, the thickness T of the ceramic green sheet is 1 μm ≤ T ≤ 2 μm.

[0043] Preferably, the multilayer ceramic capacitor is a multilayer chip ceramic capacitor.

[0044] Preferably, the method for preparing the multilayer ceramic capacitor comprises the following steps: The dielectric slurry is processed into a shape to obtain a ceramic green sheet; a conductive film is prepared on the surface of the ceramic green sheet; a plurality of layers of ceramic green sheets containing the conductive film are stacked, a ceramic green sheet without the conductive film is placed on the top layer, and the layers are crimped and cut to obtain a multilayer ceramic laminate; the multilayer ceramic laminate is sintered to obtain a ceramic sintered body; external electrodes are formed on both end surfaces of the ceramic sintered body, and a plated film is formed on the surface of the external electrode by electrolytic plating to obtain the multilayer ceramic capacitor.

[0045] More preferably, the conductive film on the surface of the ceramic green sheet is obtained by screen printing a conductive paste; and the pattern of the conductive film is given according to actual needs of the product.

[0046] More preferably, the conductive paste is a conductive paste for internal electrodes; the conductive paste for internal electrodes includes a base metal material.

[0047] More preferably, the number of stacked layers and the stacking direction of the ceramic green sheets are given according to actual requirements of the product.

[0048] More preferably, the method for processing and molding the medium slurry includes a lip coating method or a doctor blade method.

[0049] Among them, the scraper method belongs to the casting process.

[0050] More preferably, the sintering temperature of the multi-layer ceramic laminate is 1100-1300° C.; the sintering time is 0.1-2.5 h, more preferably 1-2.5 h.

[0051] More preferably, the step of forming external electrodes on both end surfaces of the ceramic sintered body comprises: coating conductive paste for external electrodes on both end surfaces of the ceramic sintered body, and baking the paste to form the external electrodes.

[0052] More preferably, the conductive paste for the external electrode comprises at least one of silver, copper, and a silver-copper alloy.

[0053] More preferably, the baking treatment is performed at a temperature of 600-900°C.

[0054] More preferably, the plating film includes a first plating film and a second plating film; the first plating film includes at least one of Ni, Cu, and Ni-Cu alloy; and the second plating film includes at least one of solder and tin.

[0055] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The dielectric material of the present invention uses three types of dielectric powders with different particle sizes for grading, controls the particle size distribution of dielectric powder A, dielectric powder B and dielectric powder C, and forms a tight stacking through grading, thereby solving the problem of loose stacking between dielectric powders due to the reduction of dielectric powder size.

[0056] (2) The dielectric material used in traditional multilayer ceramic capacitors is usually composed of powders with a single particle size. The present invention achieves the most compact stacking of dielectric materials by grading three types of powders and further controlling the average particle size relationship and mass content relationship of the three types of dielectric powders.

[0057] (3) The dielectric material of the present invention can be densely stacked and can be prepared into a dielectric slurry for use in the preparation of multilayer ceramic capacitors, thereby reducing the amount of pressing deformation during the preparation of multilayer ceramic capacitors, improving the density and reliability of the film tape of the multilayer ceramic capacitor, and avoiding problems such as severe deformation of the film tape and high short-circuit rate of the product. The dielectric material has low cost and high operability and will not affect the product manufacturing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Schematic diagram of the gradation theory of medium powder A, medium powder B and medium powder C according to an embodiment of the present invention. DETAILED DESCRIPTION

[0059] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0060] In the following embodiments of the present invention, the dielectric powders A, B and C are all barium titanate, and their gradation theory is as follows: Figure 1 shown.

[0061] Example 1 This embodiment provides a dielectric material, and uses the dielectric material to prepare a dielectric slurry, and further prepares a multilayer chip ceramic capacitor.

[0062] The specific parameters of the dielectric material in this embodiment are shown in Table 1. The preparation method of the dielectric slurry and the multilayer ceramic capacitor includes the following steps: Prepare medium slurry: S1: Mix medium powder A, medium powder B and medium powder C according to the particle size distribution requirements in Table 1 for 6 hours to obtain a medium material; S2: Based on 100 parts by mass of the dielectric material, add 0.08 parts of dispersant sodium methylene dinaphthalene sulfonate, 25 parts of adhesive polyvinyl butyral (PVB) resin, 25 parts of organic solvent (toluene: ethanol (mass ratio) = 1:1), 0.08 parts of plasticizer dioctyl phthalate (DOP), 0.1 parts of defoaming agent polydimethylsiloxane and 15 parts of grinding media zirconium dioxide grinding balls to the dielectric material obtained in step S1, and sand grind in a sand mill for 10 hours, discharge the material, and obtain a dielectric slurry.

[0063] Preparation of multilayer ceramic capacitors: S3: The dielectric slurry obtained in the above step S2 is subjected to tape casting by a doctor blade method to obtain a ceramic green sheet with a thickness of 1.33 μm; S4: using Ni metal conductive paste to perform screen printing on the ceramic green sheet obtained in step S3 according to the actual required pattern, so as to obtain a conductive film with a given pattern on the surface of the ceramic green sheet; S5: stacking 420 layers of ceramic green sheets containing a conductive film in a given direction, with the top layer being a ceramic green sheet without a conductive film, and pressing and cutting to obtain a multi-layer ceramic laminate; S6: sintering the multilayer ceramic laminate prepared in step S5 at a sintering temperature of 1100° C. for 1 h to obtain a ceramic sintered body; S7: The two end surfaces of the ceramic sintered body prepared in step S6 are coated with conductive paste for external electrodes, and then baked at 700°C to form external electrodes; a first coating Ni-Cu alloy and a second coating Sn are plated on the surface of the external electrodes by electrolysis to obtain a multilayer ceramic capacitor.

[0064] The thickness of ceramic green sheets and the average particle size R of dielectric powder A in multilayer ceramic capacitors A See Table 1 for the relationship.

[0065] Embodiments 2 to 17 The differences between the dielectric materials of Examples 2 to 17 and Example 1 are shown in Table 1. The preparation methods of the dielectric slurry and the multilayer ceramic capacitor are the same as those of Example 1.

[0066] The thickness of ceramic green sheets and the average particle size R of dielectric powder A in multilayer ceramic capacitors A See Table 1 for the relationship.

[0067] Table 1 Dielectric materials and ceramic green sheet thickness parameters of Examples 1 to 17

[0068] In Table 1, D max / R and D min / R respectively represent the ratio of the maximum particle size, the minimum particle size and the average particle size in the dielectric material; R A , R B , R C are the average particle sizes of medium powder A, medium powder B, and medium powder C respectively; R A / T represents the ratio of the average particle size of dielectric powder A to the thickness of the ceramic green sheet; A, B, C represent dielectric powder A, dielectric powder B, and dielectric powder C, respectively.

[0069] Comparative Examples 1 to 11 The differences between the dielectric materials of Comparative Examples 1 to 11 and Example 1 are shown in Table 2. The preparation methods of the dielectric slurry and the multilayer ceramic capacitor are the same as those of Example 1.

[0070] The thickness of ceramic green sheets and the average particle size R of dielectric powder A in multilayer ceramic capacitors A See Table 2 for the relationship.

[0071] Table 2 Parameters of dielectric materials and ceramic green sheet thickness in Comparative Examples 1 to 11

[0072] In Table 2, D max / R and D min / R respectively represent the ratio of the maximum particle size, the minimum particle size and the average particle size in the dielectric material; R A , R B , R C are the average particle sizes of medium powder A, medium powder B, and medium powder C respectively; R A / T represents the ratio of the average particle size of dielectric powder A to the thickness of the ceramic green sheet; A, B, C represent dielectric powder A, dielectric powder B, and dielectric powder C, respectively.

[0073] It should be noted that the average particle size R of the medium powder A in Examples 1 to 13, Examples 16 to 17, Comparative Examples 1 to 6 and Comparative Examples 9 to 11 is Ais 200nm, Example 14 is 133nm, Example 15 is 266nm, Comparative Example 7 is 107nm, and Comparative Example 8 is 333nm.

[0074] Results The above embodiments and comparative examples were subjected to performance tests, and the test methods were as follows: 1. Deformation of the bar during lamination: In the embodiment and the comparative example, the same lamination parameters were used, with 10 layers of upper and lower cover sheets, 420 layers of printed sheets, and lamination using a hydrostatic press, water temperature 65°C, pressure 200MPa, and hydrostatic press time 3600s. The thickness of the same bar and the same area before and after lamination was tested to obtain the lamination deformation. The smaller the deformation, the higher the stacking density of the film tape.

[0075] 2. Mean time to failure (MTTF): The mean time to failure of the multilayer ceramic capacitors prepared in the examples and comparative examples was tested at 150°C / 38V voltage, with a sample size of 120. The longer the mean time to failure, the better the product reliability.

[0076] 3. Membrane density: Use a focused ion beam microscope to prepare membrane cross-section samples and calculate the membrane packing density. The larger the value, the better the membrane density.

[0077] The test results are shown in Table 3 below.

[0078] Table 3 Performance test results of the embodiments and comparative examples

[0079] It can be seen from Table 3 that the multilayer ceramic capacitor (MLCC) prepared by the dielectric material obtained in the present invention has low deformation, high reliability and high film tape density. The block pressing deformation does not exceed 13.7%, and the lowest reaches 11.49%; the average failure time is not less than 5.97h, and the highest reaches 7.22h; the film tape density is not less than 94.39%, and the highest reaches 95.69%.

[0080] It can be seen from Examples 1 to 3 and Comparative Example 1 that if the D of the medium powder A max / R is too large and there are large particles in the film tape. After the product is sintered, these large particles will reduce the insulation resistance of the product and eventually lead to poor product performance.

[0081] By comparing Example 1, Examples 4-5 and Comparative Example 2, it can be found that if the Dmin / R of the dielectric powder A is too small, it means that small particles exist in the membrane tape. These small particles have high sintering activity during the sintering process, resulting in deterioration of product performance. From the comparison between Example 1, Examples 6 to 9 and Comparative Examples 3 to 4, it can be seen that when R A / RB When the particle size of medium powder A is too large or medium powder B is too small, medium powder B and C will not be filled densely enough. A / R B When it is too small, that is, the particle size of medium powder A is too small or medium powder B is too large, it will interfere with the filling of medium powder B, which will lead to low packing density of the membrane tape and ultimately reduce the performance of the product. It can be seen from Example 1, Examples 10 to 13 and Comparative Examples 5 to 6 that medium powder C with a particle size that is too small or too large will result in a low packing density of the membrane tape, ultimately deteriorating product performance. This is because if the particle size of medium powder C is too small, it will lead to a low filling density, while if the particle size of medium powder C is too large, it will interfere with the stacking of A and B powders. By comparing Example 1, Examples 14-15 and Comparative Examples 7-8, when the thickness of the ceramic green sheets is 1.33 μm, the average particle size R of the dielectric powder A is A If the thickness T is too large relative to the ceramic green sheet, the powder packing density will be low, there will be many gaps between the powders, the surface roughness of the cast film will be low, and the average particle size R of the dielectric powder A will be A If it is too small, it will lead to high sintering activity of the product. Both situations will reduce the performance of the MLCC product. From the comparison of Example 1 and Comparative Examples 10-11, it can be seen that compared with the MLCC products prepared from double-particle size grading and single-particle size powders, the MLCC products with three-particle size grading have higher bulk density, so the density of the cast film tape is higher, and the compression deformation of the MLCC raw material under hydrostatic pressure is minimal.

[0082] In summary, the dielectric material of the present invention achieves the most compact stacking, solves the problem of loose stacking between dielectric powders due to the reduction in dielectric powder size, can be used as a dielectric slurry in the preparation of multilayer ceramic capacitors, reduces the amount of pressing deformation during the preparation of multilayer ceramic capacitors, improves the density and reliability of the film tape of multilayer ceramic capacitors, avoids problems such as severe deformation of the film tape and high short circuit rate of products, has low cost and high operability, and will not affect the product process flow.

[0083] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A dielectric material, characterized in that: The medium powders include medium powder A, medium powder B and medium powder C; the average particle sizes of the medium powders A, B and C are R A , R B , R C ; Among them, R A >R B >R C ; The particle size distributions of the medium powder A, medium powder B, and medium powder C all satisfy the following relationship: The maximum particle size is 2 to 2.5 times the average particle size; The minimum particle size is 1 / 4~1 / 3 of the average particle size.

2. The dielectric material according to claim 1, characterized in that The R A , R B , R C Satisfy at least one of the following a)~b): a) R A / R B =2~2.8; b) R A / R C =9~9.6。 3. The dielectric material according to claim 2, characterized in that: The R A / R B =2.2~2.6; and / or, the R A / R C =9.2~9.

4.

4. The dielectric material according to claim 1 or 2, characterized in that: The average particle size R of the medium powder A A It is 80~300nm.

5. The dielectric material according to claim 1 or 2, characterized in that: In the dielectric material, the mass content of dielectric powder A is 91-96%; And / or, the mass content of medium powder B is 4-9%; And / or, the mass content of medium powder C is 0.08~0.2%.

6. The dielectric material according to claim 1, characterized in that The dielectric powder A, dielectric powder B and dielectric powder C are independently selected from at least one of barium titanate, strontium titanate, barium zirconate, strontium zirconate and barium strontium zirconate titanate.

7. A dielectric slurry, characterized in that: Comprising the dielectric material according to any one of claims 1 to 6.

8. The dielectric slurry according to claim 7, characterized in that: The medium slurry also includes a dispersant, a binder, an organic solvent, a plasticizer, a defoamer and a grinding medium.

9. A multilayer ceramic capacitor, characterized in that: It comprises the dielectric material according to any one of claims 1 to 6, or the dielectric slurry according to any one of claims 7 to 8.

10. The multilayer ceramic capacitor according to claim 9, wherein: Also includes a ceramic green sheet formed by a dielectric slurry; an average particle size R of the dielectric powder A A The thickness of the ceramic green sheet T satisfies the following relationship: 0.1T≤R A ≤0.2T.